The Function of female representatives in the sixth term of the Islamic Council )1379-1383/2000-2004 - Nooraldin Nemati (زن در فرهنگ و هنر, 2023)
Parliament in the modern structure of politics represents the popular will and thus holds a special place. How women performed in the parliament is here a topic of special interest. The Iranian constitution gives extensive powers to the parliament members and several principles of the constitution emphasize the women’s rights, empowering women and creating job opportunities for women under Islamic standards. The sixth term of the parliament was formed by a majority of Reformist representatives elected by a large number of voters. The elected women in this parliament all had higher education degrees. A women’s fraction was created and with the support of the other members of the parliament, important laws and reforms were made in areas like job, education, family support, equal pay, and joining the convention for eliminating discrimination against women, all intended to improve the legal status of women. The present research examines the following question: how did the women representatives on the Parliament contributed to this reform and what means they used. We will study how the formation of the women’s fraction and proposing laws and reforms regarding the improvement of employment for women, education, family support, and protecting the children in the family contributed to this legal reform and if it consequently brought any change to the society.